Suitability evaluation of minor millets in Ponnaniyar basin soils of Tiruchirapalli, Tamil Nadu - SABAREESHWARI, V.; BASKAR, M. (Journal of Soil and Water Conservation, 2020)
Minor millets suitability was evaluated for five pedons on the basis of variation in physiography, parent materials, and soil nutrients in Ponnaniyar basin soils of Tiruchirapalli, Tamil Nadu. The pedons (P) were developed by non-calcareous gneiss with feldspar (P1), granite and feldspar intermingled (P2), weathered gneiss (P3), weathered quartz and felspatic gneiss (P4) and gneiss with lime parent materials (P5) and classified as Vertisol (P3, P5), Inceptisol (P1, P2) and Alfisol (P4). In general, sand, silt and clay contents ranged from 16.0 to 71.6, 9.0 to 49.5 and 12.3 to 55.3% in different horizons, respectively. Soils were calcareous and moderately alkaline to strongly alkaline in reaction. The organic carbon ranged from 0.13 to 0.39 g kg-1 and cation exchange capacity from 16.23 to 19.91 cmol(p+)kg-1 soil. Soils were low, medium and high in available N, P and K, respectively. All five pedons are highly suitable (S1) for minor millet cultivation.